Peran guru sebagai mediator nilai pancasila dalam kelas sd: studi kualitatif - Auliya Aenul Hayati; Retno Permata Agustin; Lulus Nisa Rahayu; Widianti Widianti (Jurnal Pendidikan Dasar, 2026)
Abstract: The application of Pancasila values is very important in shaping the character, morals, and national identity of students. Qualitative research through a case study at SDN 1 Asem, Cirebon City, shows that teachers are not only conveyors of material, but also active character builders who facilitate the internalization of Pancasila values through interactive learning methods. Key Findings Questionnaire analysis reveals that the internalization of Pancasila values among students is in the strong category with an average percentage of 74-79%, namely the indicators of Belief in God (78%), humanity (79%), unity (79%), and democracy (74%). These findings indicate the role of teachers in creating a conducive school environment through contextual and participatory mediation. The use of strategies such as discussions, collaborative projects, and role modeling helps students implement Pancasila values in their daily lives. Continuous training for teachers and the integration of Pancasila values into all learning and social activities at school are recommended for effective character education.